Native Mycorrhizh-Forming Fungi Associated with Cultivated Forage Plants in the Central Valley Of Catamarca, Argentina (Global Journal of Science Frontier Research, 2022)
Mycorrhizae are a symbiosis between the roots of some plants and certain soil fungi, where both participants in this association obtain benefits. The plant provides the fungus with carbohydrates, proteins, and lipids, and in turn, the fungus allows the plant to better uptake nutrients from the soil and water. The objective was to determine the existence of mycorrhizal associations between native fungi and forage crops in the Central Valley of Catamarca. Root colonization of Melilotus officinalis, Avena sativa, Hordeum vulgare, Secale cereale, Panicum maximum, and Cenchrus ciliaris from field crops in the Central Valley of Catamarcawas studied. Fungal infection or colonization was quantified using the line intersection method and the frequency of appearance of fungal structures. Endomycorrhizal structures of the arbuscular vesicle type were observed, with continuous mycorrhizal hyphae, some of them with rosary lipids inside and vesicles with fat globules. In addition, dark septate endophytic fungi were observed. The association of mycorrhizae is described in six forage species cultivated in the Central Valley of Catamarca and the co-occurrence of arbusculo-vesicular mycorrhizae and native dark septate endophytes.
Keywords: oatmeal; barley; rye; gatton panic; buffalo-grass